Solve the following equation. (First rewrite the equation so that the right hand side equals zero.)
(a) x squared = -x
(b) x squared - 10x = 35 = 10
1. Rewrite the equation such that one side of it equals zero.
2. Factorize the term. With your problems you'll get two factors.
3. Use the property: A product equals zero if one (or more) factor(s) equals zero.
$\displaystyle x^2=-x~\implies~x^2+x=0~\implies~x(x+1)=0~\implies~x = 0~\vee~x+1=0$
Therefore the equation has the solution: $\displaystyle x = 0~\vee~x = -1$
The second problem has to be done similarly. (I assume that the first = should be a +)